The new Sunset western garden book : the ultimate gardening guide - Brenzel, Kathleen Norris (Time Home Entertainment Inc., 2012)
"The editors of Sunset-the West's most trusted source of gardening information for more than 80 years-have completely redesigned and updated The Western Garden Book in this new 2012 Ninth Edition. This edition includes a fresh new look, thousands of color photographs, fresh illustrations, and an easy-to-follow format." --Publisher.